A votação eletrônica e a representação discente nos Conselhos Superiores da Universidade Federal de São Carlos - Salmázio, Flávia Caroline Augusto (2020)
Electoral processes for choosing representatives are a fundamental part of democracy. In order to safeguard the reliability of these processes, the study of the types of electoral systems is of great importance. Still, fundamental for the formation of people and for science, the Brazilian Federal Universities have consolidated internal processes for choosing representative. The Superior Councils are the bodies where collectively the most important decisions are made by Universities and the Federal University of São Carlos (UFSCar), in particular. These Councils are composed of teachers, technical-administrative, undergraduate and graduate students, as well as representatives of the external community. In 2018, UFSCar started to adopt electronic voting in the election of representatives to the Superior Councils. The present work aims to portray how student representation occurs at the UFSCar Superior Councils with regard to their participation in the composition, the importance given to this representation and the effects of the adoption of electronic voting in the election of representatives; still, it is verified, in the present work, by which systems other Universities have been holding their elections. As a result, it was found that there was an important increase in the frequency of discussions about student elections in the UFSCar Superior Councils in the last 3 years (2017, 2018 and 2019) - in particular, in the year 2018. It was also possible to verify that the The introduction of individual electronic voting, as opposed to multiple paper voting, reduced the number of candidates, guaranteed the effective participation as voters of approximately 10% of the students and caused a greater diversity among the elected representatives regarding the Academic Center of origin. It was identified that many Federal and State Universities in São Paulo already adopt electronic voting and that the Helios Voting system, used at UFSCar, has also been implemented in several institutions. Finally, it is concluded that the adoption of individual electronic voting led to a change, for the better, in student representation within UFSCar.